Iris [videorecording (DVD)] - Dench, Judi, 1934-; Broadbent, Jim; Winslet, Kate; Bonneville, Hugh (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2002)
Adapted from the memoirs of literary critic John Bayley, the film recounts his courtship of and long marriage to British novelist Iris Murdoch. The scenario tacks back and forth from the young Iris--ready to seduce one and all with her coy command of words and sex appeal--to the elder Iris--slowly giving way to the cruel erasure of Alzheimer's.